Analysis Of The Characteristics Of Glaucoma Sufferers at Makassar Makassar Eye Hospital In 2019-2021 - Muthmainnah Al Hikmah; Rahasiah Taufik; Hastiah (RS Mata Makassar, 2024)
Background: Glaucoma is a major cause of irreversible blindness worldwide. The prevalence of glaucoma is estimated that 111.8 million people will suffer from glaucoma in 2040, so it is important to know the characteristics of glaucoma. Objective: To find out information and distribution of characteristics of glaucoma sufferers at Makassar Eye Hospital in 2019-2021. Methods: A Descriptive Retrospective study aims to determine the characteristics of glaucoma sufferers at Makassar Eye Hospital in 2019-2021 using a purposive sampling method. Results: Based on the total data collected for 207 samples, it was found that there were 105 males (50.7%) and 102 females (49.3%). The number of patients with an age range of 40-49 years was 25 people (12.1%), an age range of 50-59 years was 66 people (31.9%), an age range of 60-69 years was 81 people (39.1%) , the age range of 70-79 years was 35 people (16.1%). The number of patients with myopic refractive error was 116 people (56%), hypermetrope was 56 people (27.1%), astigmatism was 35 people (16.9%). Conclusion: Glaucoma sufferers in 2019-2021 at Makassar Eye Hospital have significant characteristics, namely the majority are men (50.7%), aged between 60-69 years, and those who suffer from myopic refractive errors (56%).